2017
DOI: 10.15171/jlms.2018.09
|View full text |Cite
|
Sign up to set email alerts
|

Bond Strength of Fiber Posts to Composite Core: Effect of Surface Treatment With Er,Cr:YSGG Laser and Thermocycling

Abstract: Introduction: This study aimed to determine the bond strength of fiber post to composite core following surface treatment with Er,Cr:YSGG laser at different powers and sandblasting with and without thermocycling. Methods: In this experimental study, 30 fiber posts (Glassix, Nordin, Switzerland) were randomly divided into 5 groups of sandblasting, no treatment and laser irradiation at 1, 1.5 and 2 W powers. Following composite filling and mounting, 1-mm thick sections were made for pushout bond strength testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Gomes et al reported that irradiation of Er,Cr:YSGG laser with 2780 nm wavelength, 150 mJ energy, 10 Hz frequency, 1.5 W power, 140 μs pulse duration and 60% water and 40% air for 60 s in non-contact mode increased the push-out bond strength of fiber posts [17]. Hashemikamangar et al evaluated the effect of surface treatment of fiber posts with Er,Cr:YSGG laser and demonstrated that irradiation of Er,Cr:YSGG laser with 1.0 and 1.5 W power, 20 Hz frequency, 140 μs pulse duration in non-contact mode with 80% water and 60% air for 30 s enhanced the micro-push-out strength of fiber posts [30]. Kurtulmus-Yilm et al reported that irradiation of Er,Cr:YSGG laser with 1.0 and 1.5 W power, 20 Hz frequency, 140 μs pulse duration and 80% water and 60% air for 30 s in non-contact mode increased the push-out bond strength of fiber posts [31].…”
Section: Discussionmentioning
confidence: 99%
“…Gomes et al reported that irradiation of Er,Cr:YSGG laser with 2780 nm wavelength, 150 mJ energy, 10 Hz frequency, 1.5 W power, 140 μs pulse duration and 60% water and 40% air for 60 s in non-contact mode increased the push-out bond strength of fiber posts [17]. Hashemikamangar et al evaluated the effect of surface treatment of fiber posts with Er,Cr:YSGG laser and demonstrated that irradiation of Er,Cr:YSGG laser with 1.0 and 1.5 W power, 20 Hz frequency, 140 μs pulse duration in non-contact mode with 80% water and 60% air for 30 s enhanced the micro-push-out strength of fiber posts [30]. Kurtulmus-Yilm et al reported that irradiation of Er,Cr:YSGG laser with 1.0 and 1.5 W power, 20 Hz frequency, 140 μs pulse duration and 80% water and 60% air for 30 s in non-contact mode increased the push-out bond strength of fiber posts [31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the strength and fracture load decreased by about 18%. Hashemikamangar et al claimed that no significant effect was detected after the thermocycling process on pushing-out bond strength between the fiber posts and resin core [ 40 ]. Moreover, the bond strength values in the thermocycled samples were slightly lower than the values in the nonthermocycled samples.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of application of hydrofluoric acid within different concentrations and on post have been investigated (12). It has been shown that the concentration of 4% (13) and 5% of acid gel for 60sec increased the bond of post .the concentration of 9.5 of HF used by Some authors (14,15) for 20sec, this results in increasing the bonding strength . In this study, 9.6 % acid was added to types of post.…”
Section: Discussionmentioning
confidence: 99%